Revisiting the South American Acanthocephalini (Hemiptera, Coreidae): Spilopleura Stål (status novum) - Olivera, Leonela (2023)
The family Coreidae is composed of some of the larger terrestrial Heteroptera, with showy colors and expansions on the legs, the antenna or the pronotum. Among the Neotropical fauna, the tribe Acanthocephalini Stål, including 18 genera, is recognized by the strongly deflexed juga, and the conspicuously projecting tylus. In the same work in which Stål established the tribe, he described two new subgenera to the genus Acanthocephala Laporte (currently synonymized under it): A. (Metapodius) (replaced for Metapodiessa Kirkaldy) and A. (Spilopleura). In the present work, the subgeneric name Spilopleura is removed from synonymy under Acanthocephala and elevated to generic rank, and the species A. parensis (Dallas) and A. ochracea Montandon are transferred therein. The genus Spilopleura status nov. and both included species are redescribed and illustrated, including characters from male and female genitalia; and a distributional map is given with the first records of the species from Argentina, Colombia, Paraguay, and Peru.